Batteries: Large‐Area Preparation of Crack‐Free Crystalline Microporous Conductive Membrane to Upgrade High Energy Lithium–Sulfur Batteries (Adv. Energy Mater. 31/2018). Issue 31 (5th November 2018) - Zang, Ying; Pei, Fei; Huang, Jiahong; Fu, Zhihua; Xu, Gang; Fang, Xiaoliang
Abstract : In article number1802052, Xiaoliang Fang, Gang Xu, and co‐workers report a facile method to fabricate a large‐areal, crack‐free, light‐weight, and conductive metal‐organic framework membrane on a Celgard separator. With an excellent polysulfide‐entrapping ability, the modified Celgard separator can significantly improve the capacity, rate capability, and cycling stability of high‐sulfur‐loading Li–S batteries.